The Effect of The STEM-PjBL Model on The Higher-Order Thinking Skills of Elementary School Students - Ika Maryani; Christina Astrianti; Vera Yuli Erviana (Universitas Negeri Malang, 2021)
The challenges of 21st-century education require higher-order thinking skills (HOTS) to exist in various fields. This study aims to determine the effect of the STEM-PjBL approach on HOTS. This research is a quasi-experimental study with the nonequivalent control group design model. The research data were obtained from 23 students of class IV A SD Muhammadiyah Macanan, Yogyakarta, as the experimental class, while the control class was 23 students from class IV B. The data collection technique used tests. The research instrument was in the form of multiple-choice test questions that had previously been validated by experts and empirical tests, which resulted in valid and reliable questions. The data analysis technique used an independent sample t-test and paired sample t-test. The results showed that the STEM-PjBL approach had a significant effect on student HOTS. There are differences in student HOTS before and after giving treatment. The differences in the HOTS’ mean were also shown in the experimental class and the control class.